The Role of Foreign Domestic Helpers in Hong Kong Chinese Children's English and Chinese Skills: A Longitudinal Study. Issue 2 (22nd December 2016) - Dulay, Katrina May; Tong, Xiuhong; McBride, Catherine
Abstract : We investigated the influence of nonparental caregivers, such as foreign domestic helpers (FDH), on the home language spoken to the child and its implications for vocabulary and word reading development in Cantonese‐ and English‐speaking bilingual children. Using data collected from ages 5 to 9, we analyzed Chinese vocabulary, Chinese character recognition, English vocabulary, and English word reading among 194 native Cantonese‐speaking children in Hong Kong with English‐speaking FDHs ( n = 46), children with Cantonese‐speaking FDHs ( n = 32), and children with no FDHs who were spoken to in Cantonese ( n = 116). Multilevel modeling results showed potential advantages in initial English vocabulary and disadvantages in initial Chinese character recognition among children in the English‐speaking FDH group, with no evidence for compounding or diminished costs or benefits over time. Results are discussed in relation to both theoretical and practical aspects of home language and literacy development.